The land question in South Africa: the challenge of transformation and redistribution - NTSEBEZA, Lungisile; Ruth Hall, Lee Smith, Stacey Gibson, Jenny Young, comPress (Cape Town : HSRC Press, 2007)
Summary: The extent to which indigenous people were dispossessed of their land by whites in South Africa under colonial rule and apartheid has no parallels on the African continent. Since the advent of democracy in 1994, issues at the heart of the land question are how to reverse this phenomenon and how a large-scale redistribution of land can contribute to transforming the economy and reducing poverty. The Land Question in South Africa debates these issues against the backdrop of a land reform programme that made limited headway in the first decade of South Africa's democracy. The authors offer a robust assessment of that programme, and raise critical questions for its future. Written by leading thinkers on the topic, this book is bound to have wide appeal among students and activists, as well as academics, researchers and policy makers.
Includes bibliographical references and index.
Adult
Keywords: South Africa; Non-fiction